"Gestión por procesos del talento Humano para la Cooperativa de Ahorro y Crédito Vinces Ltda. del Cantón Vinces, año 2013" - Salinas Mina, Katiuska Mabel (2014)
Written work contains a chapter I, introduction where the problem formulation and justification of the study, research problem is defined , Chapter II conceptual framework, discusses the theoretical framework related to the topic that describes the theoretical basis of research, we has identified and selected to develop the scientific content theme MANAGEMENT PROCESS OF HUMAN TALENT FOR COOPERATIVE SAVINGS AND CREDIT VINCES LTDA. OF CANTON VINCES , YEAR 2013 , this theoretical basis applied in the respective field of work. Chapter III describes the methodology used, activities undertaken to obtain information and results, which to our knowledge, constitute the most important aspects when evaluating the human resource front attitude to creativity and innovation existing in the Savings and Credit Cooperative. Chapter IV results, the statistics presented here, and the results have been timely porcentualizados, plotted, interpreted and discussed. Furthermore, the conclusions and recommendations where the achievements of fieldwork, synthesized previously exposed and allow us to recommend the proposal arise where different ways of dealing with problems, and implement them know which we successfully help out situations that require our creativity.